2014
DOI: 10.11002/kjfp.2014.21.5.636
|View full text |Cite
|
Sign up to set email alerts
|

Quality and storage characteristics of frankfurter sausages with added yam (Dioscorea japonica) powder

Abstract: Quality changes in frankfurter sausages with yam (Dioscorea japonica) powder added were investigated during their storage at 10°C for six weeks. The sausage samples were prepared using four concentrations of yam powder: 0% (C), 0.5% (T1), 1.0% (T2), and 2.0% (w/w) (T3). After the addition of yam powder, the crude protein contents decreased, but the crude fat and carbohydrate contents increased. The thiobarbituric acid values during the storage of the frankfurter sausages were lower in the samples with higher y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Contrary results were reported by Tan et al (2007) when evaluating Chinese sausages formulated with different fat/yam ratios (20/0, 15/5, 10/10 and 5/15%, respectively), observing low values of TBA in samples with higher fat replacement/yam, arguing that this behavior could be due to antioxidant properties of yam. For its part, Jang and Lee (2014) reported that by adding different percentages of yam starch (Dioscorea japonica) to a Frankfurt sausage, the values of TBA during the 1 st week of storage were higher in samples containing starch of yam and in the rest of the weeks were lower in the samples with higher concentrations of yam, associating this behavior to the possible presence of tocopherol and vitamin C in the starch which could contribute to antioxidant activity.…”
Section: Physicochemical Characterization Of the Sausagesmentioning
confidence: 99%
“…Contrary results were reported by Tan et al (2007) when evaluating Chinese sausages formulated with different fat/yam ratios (20/0, 15/5, 10/10 and 5/15%, respectively), observing low values of TBA in samples with higher fat replacement/yam, arguing that this behavior could be due to antioxidant properties of yam. For its part, Jang and Lee (2014) reported that by adding different percentages of yam starch (Dioscorea japonica) to a Frankfurt sausage, the values of TBA during the 1 st week of storage were higher in samples containing starch of yam and in the rest of the weeks were lower in the samples with higher concentrations of yam, associating this behavior to the possible presence of tocopherol and vitamin C in the starch which could contribute to antioxidant activity.…”
Section: Physicochemical Characterization Of the Sausagesmentioning
confidence: 99%